Analysis and Reconstruction of Diagnostic Assessment of Negotiating Text Materials in Indonesian Language Teaching Modules Class X SMA/SMK - Agniya Agniya; Siraj Lintang Wicaksono; Hasnah Setiani; Febi Putri Utami; Afsana Noor Maulida Zahro; Deby Luriawati Naryatmojo; Wagiran Wagiran (Universitas PGRI Semarang, 2023)
Diagnostic assessment aims to identify students' competencies, weaknesses, and strengths. The results are used by educators as a reference in planning learning according to the learning needs of students. The adequacy of the diagnostic assessment was assessed through analytical activities. This study aims to determine the effectiveness of the diagnostic assessment prepared by educators in three teaching modules, namely the negotiating text teaching module for SMA Negeri 4 Palembang, SMA Negeri 2 Ungaran, and SMA Negeri 1 Bae Kudus. The research method used in this research is the descriptive method. This study uses the data analysis technique of the Miles and Huberman model, which includes data reduction, data presentation, and conclusion. The analysis results include component analysis of the suitability of learning objectives, learning content, and cognitive level. Furthermore, it shows that two of the three teaching modules are compatible with the objectives and learning content. The questions for the diagnostic text in the three teaching modules still apply the Low Order Thinking Skills (LOTS) level. Diagnostic assessment discrepancies in the teaching modules are then reconstructed so that the assessment has good criteria.